2016
DOI: 10.1093/ofid/ofw028
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Clinically Significant Bacteremia in Adults Hospitalized With Falciparum Malaria

Abstract: Background. African children with severe falciparum malaria commonly have concomitant gram-negative bacteremia, but co-infection has been thought to be relatively rare in adult malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 19 publications
1
30
1
1
Order By: Relevance
“…8 However, a recent multicenter study from Myanmar identified a much higher rate of significant bacteremia in adults hospitalized with malaria than had been reported previously. 11 There were significant pathogens in the blood cultures of 13% of the patients, and, as in African children, there was a predominance of Gram-negative organisms and an association with more severe illness. Furthermore, most of the bacteremic adults in the series were not suspected of having bacterial coinfection, calling into question the WHO treatment guidelines that recommend empirical antibacterial therapy only in patients with clear clinical evidence of a complicating bacterial disease.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…8 However, a recent multicenter study from Myanmar identified a much higher rate of significant bacteremia in adults hospitalized with malaria than had been reported previously. 11 There were significant pathogens in the blood cultures of 13% of the patients, and, as in African children, there was a predominance of Gram-negative organisms and an association with more severe illness. Furthermore, most of the bacteremic adults in the series were not suspected of having bacterial coinfection, calling into question the WHO treatment guidelines that recommend empirical antibacterial therapy only in patients with clear clinical evidence of a complicating bacterial disease.…”
Section: Introductionmentioning
confidence: 88%
“…More than 75% of the cases in this series received intravenous antibiotics-usually a third-generation cephalosporin-in addition to their antimalarial therapy. 11 The fact that there was not a single death in the study among the 67 adults hospitalized with falciparum malaria-35 (52%) of whom satisfied criteria for high dependency unit admission 12 -was presented as circumstantial evidence to suggest that empirical antibacterial therapy may improve outcomes in adults with a diagnosis of severe falciparum malaria, particularly the more critically ill. 11 The present study (ANtibiotic THErapy in adults with Malaria [ANTHEM]) was devised to address this question prospectively. The dramatic fall in malaria incidence in Myanmar 13 resulted in premature termination of the study; however, the data are presented here-both separately and pooled with the results of the previously cited study-to inform clinicians working in malaria-endemic regions.…”
Section: Introductionmentioning
confidence: 97%
“…This is less plausible since other investigators found increased malaria parasitemia as least in whole blood as assessed by different methods including blood smears in relation to HIV infection [11,17,18]. Second, the observed increased severity may be due to other concomitant HIV-associated opportunistic co-infections difficult to diagnose in this relative low resource setting [3,19]. This may have been the case, considering the substantial overlap of HIV and malaria prevalence in this region.…”
Section: Discussionmentioning
confidence: 86%
“…Mais la survenue dans notre cas d'une dysurie, ainsi que l'identification d'une souche de même espèce et avec le même antibiogramme dans les urines avec production de nitrites nous conduit à confirmer le caractère pathogène de cette souche. Le lien entre accès palustre et septicémie n'est pas clair, mais certains auteurs ont évoqué la possibilité d'un déficit immunitaire transitoire concomitant de ces accès palustres (Nyein et al, 2016). Il faut aussi remarquer que la plupart des infections à SCN sont nosocomiales, même en cas d'accès palustre alors que dans notre cas cette infection est d'origine communautaire, car tous les prélèvements positifs ont été réalisés à l'admission du patient (Bruneel et al, 2010).…”
Section: Discussionunclassified